ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN PADA SUBSEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Denisa Mardiani, - (2019)
This study aims to determine the effect of Firm Size proxied by Logarithm Natural Asset, Profitability proxied with Return On Asset (ROA), and Leverage proxied by Debt to Equity Ratio (DER) toward Firm Value proxied by Price to Book Value (PBV). Population in this study are property and real estate subsector company listed in Indonesia Stock Exchange (IDX) 2015-2017. The technique of determination of the sample using the method of purposive sampling and obtained 45 property and real estate subsector companies with a research period of four years to obtain 135 units of samples. Data analysis was done using Microsoft Excel 2013 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.0 program and significance level of 5%. The result of the research shows that (1) firm size (SIZE) no significant effect on firm value (PBV), (2) profitability (ROA) has significant positive effect on firm value (PBV), (3) leverage (DER) has a significant positive effect on firm value (PBV).